ANALISIS STRUKTUR KEPRIBADIAN TOKOH DALAM CERITA PENDEK MATA YANG ENAK DI PANDANG : PERSPEKTIF PSIKOLOGIS SIGMUND FREUD - Nadinta Putri; Eny Nurhayati; Muhammad Rokib; Dhynda Maulidya Putri Rizqita; Anisa Gita Putri; Nasyila Zahra Ananta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the personality structure of the characters in Ahmad Tohari's short story "Mata yang Enak Dipandang" using Sigmund Freud's psychoanalytic perspective. The main focus of this study is to identify the dynamics of the id, ego, and superego as reflected in the characters' actions, dialogue, and inner conflicts. The method used is descriptive qualitative with content analysis techniques through a literary psychology approach. The results show that the characters' personality structure is dominated by the id, which is oriented towards fulfilling basic needs, while the ego acts as an adaptive mediator to social reality, and the superego presents as a weak moral control. The inner conflict that arises is a result of the imbalance of these three personality structures and is reinforced by external factors such as poverty and social pressure. These findings emphasize that literary works not only represent individual psychological conditions but also reflect social realities that influence the dynamics of the characters' psyches.